Botanical compositon and mass parttoning in intercrops system with corn, Brachiaria ruziziensis and pigeon pea - Schuck, Matheus Lucas (2022)
The objective of this research was to evaluate the partition of dry mass in the production of maize, Brachiaria ruziziensis and pigeon pea cultivated in intercropping. The experiment was conducted at the IFC- Campus Concordia, SC. The design was randomized blocks with repeated measures over time, with four replications, consisting of six treatments: (1) B. ruziziensis; (2) Pigeon pea; (3) Corn + pigeon pea + B. ruziziensis; (4) Corn + B. ruziziensis; (5) Corn + pigeon pea and (6) Corn. The total dry mass productivity of corn and forage species, and the partition of the mass of leaves, stalk and corn cobs at 69, 97, 118 and 160 days after sowing were determined. During the cycle there were no diﬀerences in the productivity of total dry mass, leaves and corn cobs when cultivated in intercropping with B. ruziziensis. The cultivation of intercropped corn and pigeon pea showed a total accumulation of dry mass equivalent to the cultivation of single corn.